LITERATURE REVIEW ON THE EFFECTIVE USE OF GOOGLE SITE AS AN INTERACTIVE MEDIUM IN ISLAMIC EDUCATION LEARNING - Utari, Anggie Sri; Nasution, Muhammad Irwan Padli (Institut Agama Islam Negeri (IAIN) Bone, 2024)
AbstractÂ The current rapid advancement of technology has significantly impacted various aspects of life, including the field of education. This research aims to analyze the use of Google Sites as a medium to enhance student learning outcomes. The method employed is qualitative research with a literature review approach or System Literature Review (SLR). This study aims to compare existing theories with previous theories in the research literature. The literature sources used are derived from research results or studies published in scientific articles, with articles sourced from electronic literature search engines such as Mendeley and Google Scholar. The results of the study indicate that the use of Google Sites as a learning medium in the era of technological advancement can improve student learning outcomes